Nano-ZnO Catalyzed Green and Efficient One-Pot Four-Component Synthesis of Pyranopyrazoles - Sunil U. Tekale; Sushma S. Kauthale; Kavita M. Jadhav; Rajendra P. Pawar (Journal of Chemistry)
An efficient zinc oxide nanoparticle catalyzed one-pot, four-component synthesis of 6-amino-3-methyl-5-cyano-4-aryl-1,4-dihydropyrano[2,3-c]pyrazoles from aromatic aldehyde, malononitrile, ethyl acetoacetate, and hydrazine hydrate in aqueous medium is described. Since water was employed as the reaction medium, it serves as a green route for the synthesis of pyrano[2,3-c]pyrazoles. The advantages associated with the present protocol include nonchromatographic purification technique, use of recyclable heterogeneous nano-ZnO catalyst in aqueous medium, and short reaction time. It combines successfully the synergistic effect of green chemistry with nanocatalysis.